THE LEGAL BASIS OF THE DEBT POLICY OF THE REPUBLIC OF UZBEKISTAN - Nigmatullayeva Shakhnoza (KONFERENSIYALAR, 2025)
The Republic of Uzbekistan has been developing its debt policy since its independence in 1991. This policy is crucial for maintaining the country’s economic stability and fostering sustainable development. This article examines the legal frameworks and institutional arrangements that underpin Uzbekistan’s debt policy. It provides an analysis of the legislation governing public debt, the roles of various government bodies, and the mechanisms for debt management. Furthermore, the article explores the challenges and opportunities faced by Uzbekistan in managing its public debt and suggests potential improvements to the existing legal structures.